Mucopolysaccharidosis type I (Hurler syndrome) and anesthesia: the impact of bone marrow transplantation, enzyme replacement therapy, and fiberoptic intubation on airway management - Kirkpatrick, Katherine; Ellwood, James; Walker, Robert W. M. (Pediatric anesthesia, 2012)
Summary Aim:  To assess the effect of bone marrow transplantation (BMT), enzyme replacement therapy (ERT), and a fiberoptic endotracheal intubation technique in patients with mucopolysaccharidosis type I (MPS I, Hurler syndrome). Background:  The mucopolysaccharidoses are inherited metabolic conditions with a well‐documented association with difficult airway management. We present the largest series to date of patients with Hurler syndrome (MPS I) and look at the impact of new treatments, such as BMT and ERT, on anesthesia and airway management. Methods/Materials:  We carried out a retrospective chart review of patients with MPSI undergoing anesthesia over 9 years at the Royal Manchester Children’s Hospital. Data were collected on incidence of difficult and failed intubation and airway difficulties under anesthesia. Results:  There were 39 patients identified, of which 20 had the attenuated form of MPS I and received ERT, 18 were treated by BMT and one patient received neither treatment. These patients had a total of 114 general anesthetics for 141 procedures. The incidence of airway complications overall is lower than previously reported at 31%. Patients with the attenuated form of the disease on ERT still have a high incidence of airway problems at 57% and a failed intubation rate of 3%. BMT patients on the other hand have a much lower incidence of airway complications at 14%, and there were no failed intubations in this group. Conclusions:  Managing the MPS1 patient continues to be a challenge but with treatment and newer forms of airway management it is improving.